Use of flue gas desulfurization gypsum for the removal of off-flavor compounds in fish pond water - Niwooti Whangchai (2018)
© 2016, Int. J. of GEOMATE. All rights reserved. Accumulation of off-flavor in fish flesh caused by the presence of geosmin and 2-methylisoborneol (MIB) in pond waters is a worldwide quality problem in aquaculture. This study investigated the effectiveness of synthetic flue gas desulfurization gypsum, (FGDG) a cheap and readily soluble material from coal-fired electric utilities, for the removal of off flavor substances: geosmin and MIB, in fish pond water. Water samples from fish ponds were spiked with known concentrations of geosmin and MIB and varying amounts of FGDG (0, 200, 400 and 600 mg/L) were added to compare the removal rates of geosmin and MIB, chlorophyll a levels and orthophosphate. The experiment was conducted for 9 days. It was revealed that FGDG had significantly reduced both geosmin and MIB in spiked pond waters when compared with the control (0 mg/L) (P<0.05). The highest removal rate of geosmin (63.41%) was found when 600 mg/L of CFG was used after 9 days. However, the removal rate of geosmin at 200 and 400 mg/L FGDG was not significantly (P>0.05) different from 600 mg/L. The highest removal rate of MIB (75.63%) was found with the treatment with 400 mg/L CFG after 6 days. In addition, 200 mg/L FGDG was also highly effective in reducing chlorophyll a and orthophosphate concentration through calcium phosphate precipitation. It was suggested that 200 mg/L FGDG is the suitable dose to apply for the removal of off-flavor compounds in fish pond waters.